Development of Digital Payments as Moderation of Business Units - Shantilawati, Irma; Mayanti, Yuni; Hasanah, Depi (IJESS International Journal of Education and Social Science, 2024)
In line with the development of current trends, not only is meeting needs made easier, but in terms of payment transactions, it is also increasingly developing where people no longer have to provide physical money. People need convenience in terms of fulfilling their needs, as well as in terms of payment transactions, both from the consumer and seller side, so the current convenience requires people to use cashless more in every payment transaction. Therefore, the use of QRIS technology as Digital Payment is a positive trend for business actors in Indonesia and consumers. The research results show that QRIS has a positive and significant effect on consumer decisions in using QRIS transactions. However, there are obstacles faced, namely that not all consumers understand how to use QRIS and not all business actors also use QRIS. So there are difficulties for consumers who do not understand the ease of cashless payment transactions. The method used in the research uses quantitative data targeting MSMEs in Indonesia. From this background, the author conducted research with the title Digital Payment Development as Business Unit Moderation (Case Study of MSMEs in Indonesia).